Microbiological evaluation of Escherichia coli in cuts of beef (ground) sold in the Municipalities of Valença and Vassouras, RJ (Research, Society and Development, 2020)
The importance of beef (ground) in human food and the concern to offer an innocuous food that is incapable of transmitting diseases led to the development of this study, which aimed to evaluate the microbiological quality, the antimicrobial sensitivity profile and the hygienic-sanitary conditions in samples of beef (ground), sold in the Municipalities of Valença and Vassouras, RJ. Samples were carried out in 20 commercial establishments, which offer ground meat under conditions of consumption and analyzed according to the coliform quantification technique in MPN/g. The antimicrobial profile of Escherichia coli isolates was submitted to susceptibility tests to tetracycline (30μg), ampicillin (10μg), cephalothin (30μg), gentamicin (10μg) and cefotaxime (30μg), using the disk-diffusion method. The assessment of hygienic-sanitary conditions, on the other hand, was based on pre-established observation criteria in a model questionnaire. The total coliform indices were greater than 240 MPN/g in 90% of the analyzed samples and 55% of the samples had indices greater than 240 MPN/g for thermotolerant coliforms, and the Municipality of Valença revealed 40% of contamination within the sample universe. The evaluation of the antimicrobial profile for the antibiotic cefotaxime showed a greater spectrum of action for strains of Escherichia coli isolated from the samples, while the highest index of resistance was observed for the antibiotic cephalothin. The evaluation of hygienic-sanitary conditions was considered unsatisfactory in relation to the handling of meat, which makes this type of food a potential cause of food poisoning.